Passage of positively and negatively charged particles through straight and bent nanotubes - Greenenko, A.A.; Shul’ga, N.F. (Вопросы атомной науки и техники, 2001)
Passage of high-energy charged particles through oriented crystals and nanotubes is investigated. It is shown that the particle passage through crystals and nanotubes may to be described in the same manner. The possibility of positively and negatively charged particle deflection by bent nanotube due to axial channelling phenomenon is demonstrated. Computer simulation results for relativistic charged particle beam passage through straight and bent nanotubes are presented.